Choosing Action Games Appropriate to the Age of Preschoolers - Pardaev Bakhrom Pulatovich (Periodica Journal, 2022)
The article discusses the suitability of mobile games for a child's age, considering the child's age and physical characteristics when choosing a game. In the process of choosing an active game, several types of active games were shown to children, taking into account their speed, agility, and endurance.
Keywords: game; quickness; agility; development of the child